Need Analysis Seguyub Lasem Dance Media in the Feminine Stigma of Dance Learning for Middle Shool Students - Agustina Ayu Andira; Wahyu Lestari; Hartono Hartono (Universitas Muhammadiyah Enrekang, 2024)
Practical dance learning at school is often stigmatizes as feminine by junior high school students, especially male students. Seguyub Lasem Dance Media Video is the development of dance learning media that uses YouTube as a learning platform with the aim of increasing students' interest in learning, eliminating the stigma of femininity in the dance, and helping students practice the Profil Pelajar Pacasila character education. The aim of the Analysis of Media Needs for the Seguyub Lasem Dance Video in the Feminine Stigma of Dance Learning for Middle School Students research is to describe students' learning interest in learning dance and to describe the media needs analysis for the Seguyub Lasem Dance video. The data collection techniques used were observation, interviews and documentation. The conclusion of the research is that teachers and students need the Seguyub Lasem Dance video media to increase students' interest in learning, eliminate the stigma of femininity in the art of dance, and help students practice the Profil Pelajar Pancasila character education.. Keywords: Need analysis, dance learning, feminine stigma